2004
DOI: 10.1002/neu.20007
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide modulates local reflexes of the tailfan of the crayfish

Abstract: Electrical stimulation of sensory neurons that innervate receptors on the tailfan of crayfish evokes a reflex response of motor neurons that produce movements of the blades of the tailfan, the uropods. We analyzed the modulatory effects of nitric oxide (NO) on the spike frequency of the reflex response. Bath application of L-arginine and SNAP, which elevate endogenous and exogenous NO levels, increased the frequency of the evoked response, whereas the application of L-NAME and PTIO, which reduce NO levels, dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…In the vertebrate brain, NO is involved in synaptogenesis and in the synaptic plasticity that occurs during brain development, learning, memory, and disease (Boehning and Snyder, 2003;Keynes and Garthwaite, 2004). In invertebrates, NO is involved in rhythm generation in the stomatogastric system of mollusks (Park et al, 1998;Straub et al, 2007), crayfish (Stein et al, 2005), and locusts (Rand et al, 2008), and a role for NO has been shown in invertebrate sensory-motor processing, e.g., in the crayfish (Araki et al, 2004). In mollusk odor processing, NO is involved in controlling the periodic oscillations necessary for olfactory discrimination and learning (Gelperin, 1994;Watanabe et al, 2008).…”
mentioning
confidence: 98%
“…In the vertebrate brain, NO is involved in synaptogenesis and in the synaptic plasticity that occurs during brain development, learning, memory, and disease (Boehning and Snyder, 2003;Keynes and Garthwaite, 2004). In invertebrates, NO is involved in rhythm generation in the stomatogastric system of mollusks (Park et al, 1998;Straub et al, 2007), crayfish (Stein et al, 2005), and locusts (Rand et al, 2008), and a role for NO has been shown in invertebrate sensory-motor processing, e.g., in the crayfish (Araki et al, 2004). In mollusk odor processing, NO is involved in controlling the periodic oscillations necessary for olfactory discrimination and learning (Gelperin, 1994;Watanabe et al, 2008).…”
mentioning
confidence: 98%
“…In our study, these appeared to be the neurons that display maximum NADPH-d activity shortly after injury, and iNOS immunoreactivity thereafter. Using NOS donors and inhibitors, Araki and colleagues showed that NO enhances the activity of the motoneurons modulating the local tailfan reflexes in the crayfish (Araki et al, 2004). This suggests that NOsignaling, which is enhanced in the thoracic ganglion of shore crabs in response to nociceptive chemical stimulation, could be involved not only in sensory processing but also in motor program modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Some axons projecting from nerve 1 of the abdominal ganglia are immunopositive (H. Aonuma, personal communication). An NO-cGMP pathway has been widely reported in many sensory and motor systems in both vertebrates and invertebrates (Bawin et al, 1994;Bicker and Schmachtenberg, 1997;Araki et al, 2004;Moroz et al, 2004;Newland and Yates, 2007). Newland and Yates (Newland and Yates, 2007) show that bath application of the generic protein kinase inhibitor H-7 and a selective cGMP-dependent protein kinase (PKG) inhibitor KT-5823 reduced the frequency of the oviposition digging rhythm of the locust.…”
Section: Research Articlementioning
confidence: 98%
“…These drugs were prepared prior to application and used within 5 min. The concentration of drugs used in this study was based on Araki et al (Araki et al, 2004;Araki et al, 2005).…”
Section: Preparation Of Pharmacological Agentsmentioning
confidence: 99%
See 1 more Smart Citation